2010
DOI: 10.1093/toxsci/kfq175
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Iron Mobilization and Induction of the Mitochondrial Permeability Transition in Acetaminophen-Induced Toxicity to Mouse Hepatocytes

Abstract: Acetaminophen induces the mitochondrial permeability transition (MPT) in hepatocytes. Reactive oxygen species (ROS) trigger the MPT and play an important role in AAP-induced hepatocellular injury. Because iron is a catalyst for ROS formation, our aim was to investigate the role of chelatable iron in MPT-dependent acetaminophen toxicity to mouse hepatocytes. Hepatocytes were isolated from fasted male C3Heb/FeJ mice. Necrotic cell killing was determined by propidium iodide fluorometry. Mitochondrial membrane pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 27 publications
8
86
0
Order By: Relevance
“…At higher Pc 4 (1.5 pmol/mg), PDT induced substantial cell killing in sensitive UMSCC22A cells, and bafilomycin did not further enhance killing since the UMSCC22 cells were already very sensitive to the higher Pc 4 dose. We obtained similar results with another agent, chloroquine, which, similar to bafilomycin, causes lysosomal alkalinization (data not shown) (28,29). Bafilomycin and chloroquine induce lysosomal alkalinization by different mechanisms: bafilomycin inhibits V-ATPase, whereas chloroquine is a weak base that accumulates into lysosomes to collapse the acidic pH gradient.…”
Section: Cellular Uptake and Subcellular Localization Of Pc 4 In Headsupporting
confidence: 73%
“…At higher Pc 4 (1.5 pmol/mg), PDT induced substantial cell killing in sensitive UMSCC22A cells, and bafilomycin did not further enhance killing since the UMSCC22 cells were already very sensitive to the higher Pc 4 dose. We obtained similar results with another agent, chloroquine, which, similar to bafilomycin, causes lysosomal alkalinization (data not shown) (28,29). Bafilomycin and chloroquine induce lysosomal alkalinization by different mechanisms: bafilomycin inhibits V-ATPase, whereas chloroquine is a weak base that accumulates into lysosomes to collapse the acidic pH gradient.…”
Section: Cellular Uptake and Subcellular Localization Of Pc 4 In Headsupporting
confidence: 73%
“…However, Schisandra chinensis may be able to treat acute liver injury though protection of the mitochondria. Disruption of lysosomes in hepatocytes following acetaminophen treatment has been observed in previous studies (13,15). Notably, Schisandra chinensis was also found to protect lysosomes in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…A breakdown of lysosomes may result in cell death by necrosis, which is associated with an increase in cytosolic acidification (14). Kon et al (15) found that mobilization of chelatable iron from lysosomes was key in acetaminophen hepatotoxicity. The formation of reactive oxygen species (ROS) increases following acetaminophen exposure, and agents that augment antioxidant defenses and scavenge ROS protect against acetaminophen toxicity in vitro and in vivo (16).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of GSK 3 also accelerated liver regeneration after APAP overdose in mice [54]. In addition to proteins, translocation of metals such as iron to the mitochondria from lysosomes also occurs in hepatocytes in vitro after an APAP overdose [55] and the influence of this will also be detailed in the next section.…”
Section: Acetaminophen Hepatotoxicitymentioning
confidence: 99%
“…Mitochondria are also a central organelle for iron metabolism [64] and iron can also induce activation of the MPT [65]. Translocation of iron from lysosomes to mitochondria does occur after APAP overdose [55], which is probably facilitated by lysosomal instability seen under these conditions [66]. Interestingly, while physiological iron import into mitochondria is thought to be mediated by the mitoferrin proteins on the inner membrane [64], transport after APAP overdose seems to be occurring through the calcium uniporter, since its inhibition prevented mitochondrial oxidant stress and loss of membrane potential [67].…”
Section: Acetaminophen Hepatotoxicitymentioning
confidence: 99%